Analisa Risiko Kelangsungan Bisnis, Pengawasan dan Evaluasi Teknologi Informasi di PT ABC - Hardha, Raymond Adrian; Wibowo, Adi; Noertjahyana, Agustinus (Jurnal Infra, 2015)
PT ABC is a company engaged in the production of reinforcedconcrete. In carrying out its business processes, the company isusing the server, network, software, hardware, PC software. Withthe disruption of one of these systems, the data processing will beannoyed at having to manually process data and perform theinput to the database after the system can run normally again.Looking at the situation and condition of PT ABC, did not rule outthe occurrence of risks such as damage to data integrity andcontinuity disruption of business processes.In this thesis conducted a risk analysis of the IT continuity andmonitoring of PT ABC. Risk analysis using the framework of ISO31000, for process analysis and its use COBIT 4.1 controlpractices, and use risk rating methodology (OWASP) forcalculating the value of risk. There are 7 risks found from analysis. One risk that has highseverity is the company did not have those who has responsibilityto monitor irregularities. Two medium risks are the company didnot have business continuity plan, and also a framework to buildthat plan. Four risks with low severity are the company did nothave an offsite backup, did not have a priority plan, no trainingfor employees to upgrade analysis skills, and never update ITcontinuity plan.